2017
DOI: 10.1038/s41598-017-00149-0
|View full text |Cite
|
Sign up to set email alerts
|

USP9X deubiquitylating enzyme maintains RAPTOR protein levels, mTORC1 signalling and proliferation in neural progenitors

Abstract: USP9X, is highly expressed in neural progenitors and, essential for neural development in mice. In humans, mutations in USP9X are associated with neurodevelopmental disorders. To understand USP9X’s role in neural progenitors, we studied the effects of altering its expression in both the human neural progenitor cell line, ReNcell VM, as well as neural stem and progenitor cells derived from Nestin-cre conditionally deleted Usp9x mice. Decreasing USP9X resulted in ReNcell VM cells arresting in G0 cell cycle phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 47 publications
1
25
2
Order By: Relevance
“…Signaling through mTORC1/S6K1, a downstream mTOR target, has been reported to act as a nutrient sensor that integrates a number of environmental signals (e.g., glucose and insulin) to contribute to the development of IR and obesity [27][28][29]. Decreased mTOR/S6K1 signaling has been shown to decrease or increase IR [29][30][31][32]. However, previous studies have reported conflicting results concerning the relationship between mTORC1 and IR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Signaling through mTORC1/S6K1, a downstream mTOR target, has been reported to act as a nutrient sensor that integrates a number of environmental signals (e.g., glucose and insulin) to contribute to the development of IR and obesity [27][28][29]. Decreased mTOR/S6K1 signaling has been shown to decrease or increase IR [29][30][31][32]. However, previous studies have reported conflicting results concerning the relationship between mTORC1 and IR.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, DOCK5-mediated regulation of the mTOR-S6K-IRS-1 pathway may represent a potential drug target for the pharmacological and genetic administration of DOCK5 to improve IR and metabolic disorders. mTORC1 contains Raptor and is sensitive to rapamycin [31,32]. Raptor is a specific and important component of mTORC1, which is a pivotal regulator for both metabolism and insulin sensitivity [30].…”
Section: Discussionmentioning
confidence: 99%
“…The embryonic neocortex is composed of multiple types of NPs and fate restricted neural cells. Therefore, to test the effect of Usp9x loss on Wnt target gene expression in a homogeneous NP population, USP9X was depleted in the human NP cell line, ReNcell VM, using doxycycline inducible shRNA against USP9X 29 . 72 hours after shRNA induction, USP9X protein was almost completely depleted in these cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ReNcell VM was obtained from Millipore (Darmstadt, Germany) and maintained according to the manufactures instructions. Doxycycline-inducible Usp9x knock-down ReNcell VMs were generated as described previously 29 , 68 .…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned above, the "core" gene set also included factors of the chromatin-remodeling complex [41], such as Nipbl, Smarcc2, and Smarca4. Besides, Usp9X has been thought to be involved in developmental processes through Wnt/β-catenin and mTOR pathways [42]. These common pathways can cause shared symptoms among FXS, ID, and ASD.…”
Section: Overlap Among Fmrp Targets Neurogenesis Id and Asd-associamentioning
confidence: 99%